Criminology and Post-Mortem Studies Analyzing Criminal Behaviour and Making Medical Decisions - Palermo, Sara; Dumache, Raluca (IntechOpen, 2021)
This book is not a handbook of criminology and forensic medicine but rather a tool that reviews socio-historical and scientific data and notes of methodology based on the different sciences aimed at the study of crime in all its many facets (sociology, jurisprudence, criminalistics, psychology, forensic neuroscience, and forensic medicine). The chapters deal with single aspects of the subject, such as juvenile delinquency, fraud, and the relationship between society, individual personality, and sexual criminal behavior. They then go into more detail, analyzing individual aspects of legal medicine in light of the evolution of the discipline between the 20th and 21st centuries, including infant and adult post-mortem examination and genetic DNA identification.